Motion and force analysis in load control type treadmill using wearable sensor system - Kondo, A.; Hirose, K.; Tsujiuchi, N.; Ito, A. (Proceedings, 2020)
In this study, we developed a load control type treadmill installed with a force plate and an automatic controller. A conventional treadmill does not measure ground reaction force, and the belt is rotated at a constant speed. The developed system can measure ground reaction force and control the belt speed by feeding back measured propulsion force. A participant can obtain the load by controlling the belt speed corresponding to the target load value. The system provides an environment close to actual motion on a road. We conducted measurement experiments on the treadmill using a wearable motion sensor system in gait and running conditions, and we estimated joint angles in gait condition. The result of the vertical and propulsion force and the joint angles indicated the difference of performance in the levels of the target load value, and the characteristics of load control type treadmill are indicated.